A Study on Using Molasses Production Waste Powder as a Green Adsorbent for Cu (II) Ions from its Aqueous Solution - Fadhel, Sahar Rihan; Ghati, Shaymaa K.; Khwedim, Kareem; Jamur, Jasim M. S. (Iraqi Journal of Science, 2025)
This study utilized low-cost agricultural waste (molasses production waste powder) to extract copper ions from aqueous solutions. The present investigation explored a range of factors that influence the adsorption process, including temperature, pH, ionic strength, contact time, quantity of adsorbent, and particle size. Spectrophotometric analysis was used to determine the solution’s absorbance both before and after the adsorption procedure. The Langmuir and Freundlich adsorption models were used to match the equilibrium data. The Freundlich model was determined to be the best isotherm model using the linear regression coefficient R2=0.9868. Thermodynamic parameters, including enthalpy, entropy, and Gibbs free energy, were calculated for the continuous adsorption process, exothermic behavior of the system was observed by the heavy ion’s adsorption process results on the green adsorbent. The process is good especially at low concentration in aqueous solutions.